Thermoelectric characteristics of glass fibers coated with ZnO and Al-doped ZnO. (December 2017) - Park, Yoonbeom; Cho, Kyoungah; Kim, Sangsig
Graphical abstract: Highlights: We fabricated glass fibers coated with ZnO and ZnO:Al. We investigated thermoelectric properties of ZnO- and ZnO:Al-coated glass fibers. Differences in morphology cause differences in thermoelectric characteristics. Clusters of ZnO:Al films cause the increase of the Seebeck coefficient. Abstract: In this study, we investigate the thermoelectric characteristics of glass fibers coated with bare and Al-doped ZnO (ZnO:Al). The ZnO- and ZnO:Al-coated fibers generate maximum Seebeck voltages of −478.3 and −1057.8 μV at temperature differences of 4.5 and 4.3 K, respectively. The Seebeck coefficient increases but the electrical conductivity decreases upon doping of Al ions into ZnO. The grain boundaries present on the ZnO:Al-coated fibers have an adverse effect on their electrical conductivity, but contribute to their increased Seebeck coefficient. The power factor of the ZnO:Al-coated fibers is over three times as large as that of the ZnO-coated fibers.